FUNGSI TEKS “INILAH KITAB MAULUD” KARYA SYAIKH H. ABDUL SALAM IMAM BAGI PENGANUT ALIRAN TAREKAT SYATTARIYAH DI JORONG PULAI, KECAMATAN SITIUNG, KABUPATEN DHARMASRAYA - Nurul Chotimah (Jurnal Elektronik WACANA ETNIK, 2012)
This paper describes manuscript “Inilah Kitab Maulud” written by Syaikh H Abdul Salam Imam. This manuscript is very important for Tarekat Syattariyah society at Jorong Pulai, Sitiung Dharmasraya. From this manuscript, people know about Mohammed SAW history. This manuscript was not accessible for all readers because written in Arab Melayu. For this reason, transliteration and transcription are necessary. After all, there are functions of this manuscript for the Syattariyah people: main source of Mohammed SAW history, unifier, and controlling the society.